Cancer Stem Cell Hypothesis: Implication for Cancer Prevention and Treatment - Meiliana, Anna; Dewi, Nurrani Mustika; Wijaya, Andi (The Indonesian Biomedical Journal, 2016)
BACKGROUND: Cancer is a disease of genomic instability, evasion of immune cells, and adaptation of the tumor cells to the changing environment. Genetic heterogeneity caused by tumors and tumor microenvironmental factors forms the basis of aggressive behavior of some cancer cell populations.CONTENT: Cancers arise in self-renewing cell populations and that the resulting cancers, like their normal organ counterparts, are composed of hierarchically organized cell populations. Self â€“ renewing â€œcancer stem cellsâ€ (CSC) maintain tumor growth and generate the diverse populations constituting the tumor bulk. CSCs in multiple tumor types have been demonstrated to be relatively resistant to radiation and chemotherapy. The clinical relevance of these studies has been supported by neoadjuvant breast cancer trials that demonstrated increases in the proportions of CSCs after therapy. The CSC hypothesis has tremendously important clinical implications.SUMMARY: In summary, a large and accumulating body of evidence supports the CSC hypothesis, which has important implications for cancer prevention and therapy. The ultimate test of this hypothesis will require clinical trials demonstrating that targeting of these pathways reduces cancer incidence and improves outcomes for patients with cancer.KEYWORDS: Somatic mutation, tumor heterogeneity, metastasis, epithelial-mesenchymal transition, CSC niche